The flying man : Otto Lilienthal, the world's first pilot - Downs, Mike (Astra Young Readers, 2022)
"Here is the little-known history of Otto Lilienthal, a daring man whose more than 2,000 successful flights inspired the Wright Brothers and other aviation pioneers. In 1862, balloons were the only way to reach the sky. But 14-year-old Otto Lilienthal didn't want to fly in balloons. He wanted to soar like a bird. Scientists, teachers, and news reporters everywhere said flying was impossible. Otto and his brother Gustav desperately wanted to prove them wrong, so they made their own wings and tried to take flight. The brothers quickly crashed, but this was just the beginning for Otto, who would spend the next 30 years of his life sketching, re-sketching, and building gliders. Over time, Otto's flights got longer. His control got better. He learned the tricks and twists of the wind. His flights even began to draw crowds. By the time of his death at age 48, Otto had made more than 2,000 successful glider flights. He was the first person in history to spend this much time in the air, earning the title of the world's first pilot and paving the way for future aviation pioneers." --